Unauthorized traditional and complementary medicine and drug practices by a foreign non-physician: a case report - Yaşar Teke, Hacer; Taşkıran, Melike; Aydoğan, Halit Canberk (The Bulletin of Legal Medicine, 2025)
The widespread use of the internet and the unregulated nature of digital platforms have increased the visibility of unauthorized medical practices conducted by non-physicians, posing significant risks to public health. This study presents a case report involving a foreign national without medical training who performed Traditional and Complementary Medicine practices in Türkiye, under conditions that do not comply with health and hygiene regulations. Following a complaint submitted to the Ministry of Health Communication Center, an official inspection confirmed the absence of valid medical certification, and legal proceedings were initiated. The case reveals deficiencies in regulatory mechanisms and highlights how unmet healthcare needs among migrant communities may create space for unregulated and potentially harmful practices. Preventing such practices requires not only effective legal regulations but also strong oversight, increased public awareness, and inclusive health policies targeting migrant populations. Additionally,a multidisciplinary legal framework is essential to safeguard public health against such threats.